ADDITIONAL DESCRIPTIVE DATA FOR THE NEW COELACANTH, Latimeria menadoensis Pouyaud et al. FROM SULAWESI, INDONESIA - Soetikno Wirjoatmodjo (BRIN Publishing (Penerbit BRIN), 2002)
Morphometries and meristies data of Latimeria menadoensis, a new species of Coelacanth from Sulawesi, Indonesia (Pouyaud et al. 1999) are reported. Comparison with data of L. chalumnae as reported by McAllister and Smith (1978) and Forey (1998) are presented. Among the 22 descriptive characters only 41% are different. Some more specimens of L. menadoensis are still needed for more detail study of its morphological differences with L. chalumnae.